Age-related alterations in functional and structural networks in the brain in macaque monkeys - Ouchi, Kazuya; Yamamoto, Shinya; Obara, Makoto; Sugase-Miyamoto, Yasuko; Tsurugizawa, Tomokazu (Frontiers in Neuroanatomy, 2025)
Resting-state networks (RSNs) have been used as biomarkers of brain diseases and cognitive performance. However, age-related changes in the RSNs of macaques, a representative animal model, are still not fully understood. In this study, we measured the RSNs in macaques aged 3–20 years and investigated the age-related changes from both functional and structural perspectives. The proportion of structural connectivity in the RSNs relative to the total fibers in the whole brain significantly decreased in aged macaques, whereas functional connectivity showed an increasing trend with age. Additionally, the amplitude of low-frequency fluctuations tended to increase with age, indicating that resting-state neural activity may be more active in the RSNs may increase with age. These results indicate that structural and functional alterations in typical RSNs are age-dependent and can be a marker of aging in the macaque’s brain.